Behavioural and social drivers of COVID-19 vaccination in Vietnam: a scoping review - Jessica Kaufman; Thu Anh Nguyen; Margie Danchin; Mai Nguyen; Thao Nguyen; Tho Dang; Gregory Fox; Luong Tran; Isabella Overmars; Shiva Shrestha; Ikram Abdi; Muthu Marahajan; et al. (BMJ Open)
Background Understanding of the behavioural and social drivers (BeSD) of vaccination is key to addressing vaccine hesitancy and accessibility issues. Vietnam’s national COVID-19 vaccination programme resulted in high uptake of primary doses among adults, but lower booster doses for adults and primary doses for 5–11 years. This scoping review assessed BeSD influencing COVID-19 vaccine uptake in Vietnam to design interventions on reaching the national vaccination targets.Method We conducted a scoping review by searching PubMed, MedRxiv, LitCOVID, COVID-19 LOVE platform, WHO’s COVID-19 research database and seven dominant Vietnamese language medical journals published in English or Vietnamese between 28 December 2019 and 28 November 2022. Data were narratively synthesised and summarised according to the four components of the WHO BeSD framework. The drivers were then mapped along the timeline of COVID-19 vaccine deployment and the evolution of the pandemic in Vietnam.Results We identified 680 records, of which 39 met the inclusion criteria comprising 224 204 participants. Adults’ intention to receive COVID-19 vaccines for themselves (23 studies) ranged from 58.0% to 98.1%. Parental intention to vaccinate their under 11-year-old children (six studies) ranged from 32.8% to 79.6%. Key drivers of vaccination uptake were perceived susceptibility and severity of disease, perceived vaccine benefits and safety, healthcare worker recommendation, and positive societal perception. Commonly reported COVID-19 vaccines’ information sources (six studies) were social and mainstream media (82%–67%), television (72.7%–51.6%) and healthcare workers (47.5%–17.5%). Key drivers of COVID-19 uptake remained consistent for both adults and children despite changes in community transmission and vaccine deployment.Conclusion Key enablers of vaccine uptake for adults and children included perceived disease severity, perceived vaccine benefits and safety and healthcare worker recommendations. Future studies should assess vaccine communication targeted to these drivers, national policies and political determinants to optimise vaccine uptake.